2010
DOI: 10.1063/1.3407662
|View full text |Cite
|
Sign up to set email alerts
|

Flow, turbulence, and pollutant dispersion in urban atmospheres

Abstract: The past half century has seen an unprecedented growth of the world's urban population. While urban areas proffer the highest quality of life, they also inflict environmental degradation that pervades a multitude of space-time scales. In the atmospheric context, stressors of human ͑anthropogenic͒ origin are mainly imparted on the lower urban atmosphere and communicated to regional, global, and smaller scales via transport and turbulence processes. Conversely, changes in all scales are transmitted to urban regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(88 citation statements)
references
References 65 publications
3
85
0
Order By: Relevance
“…However, a simulation of a selected area in downtown Phoenix performed by Fernando et al [4] showed that buoyancy effects were appreciable in the middle of the street canyon; but near the ground (say z < 10 m) the buoyancy effects are hardly felt due to shear production. This also seems at odds with Louka et al [51] observations and conclusions that a thin thermal layer develops locally within a few 10's centimetres from the heated wall.…”
Section: Flow and Dispersion Under Unstable/stable Stratificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a simulation of a selected area in downtown Phoenix performed by Fernando et al [4] showed that buoyancy effects were appreciable in the middle of the street canyon; but near the ground (say z < 10 m) the buoyancy effects are hardly felt due to shear production. This also seems at odds with Louka et al [51] observations and conclusions that a thin thermal layer develops locally within a few 10's centimetres from the heated wall.…”
Section: Flow and Dispersion Under Unstable/stable Stratificationsmentioning
confidence: 99%
“…There are, of course, substantial contributions to this general area of study from laboratory (water flume and wind tunnel, e.g., [4,5]) and from the direct use of RANS (Reynods-averaged Navier Stokes equations) models, though it is often difficult to extract results as detailed as those from LES (large-eddy simulation) modeling, from such studies. We might also consider whether it is an appropriate time to reconsider our overall view of pollutant dispersion in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the urban boundary layer, the rural boundary layer, the city scale flow and the regional weather are coupled aerodynamically and thermodynamically (Britter and Hanna, 2003;Fernando et al, 2010). This again suggests that it is of great importance to consider the wind-direction effects on urban flows and dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong gradients caused by the presence of buildings and street scales, a resolution down to one metre is required (Xie and Castro, 2006;Fernando et al, 2010). Direct numerical simulation (DNS) is the most accurate computational fluid dynamics (CFD) approach (Coceal et al, 2006), but it requires enormous computer resources for high Reynolds number (Re) flows and is not suitable for urban flows in full scale.…”
Section: Introductionmentioning
confidence: 99%
“…The factitious nature of the urban topography is discussed by Fernando in [17] and fluid dynamic analyses performed in [18] describes the complexity associated with the urban topography as being the rule governing the wind resource. Indeed, this work further describes how the flow through urban RSL is highly sensitive to building morphology.…”
Section: The Urban Wind Resource and Energy Harnessing In A Turbulentmentioning
confidence: 99%